2012
DOI: 10.1002/jhm.1903
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and circadian misalignment for the hospitalist: A review

Abstract: Shift work is necessary for hospitalists to provide on‐site 24‐hour patient care. Like all shift workers, hospitalists working beyond daylight hours are subject to a misalignment between work obligations and the endogenous circadian system, which regulates sleep and alertness patterns. With chronic misalignment, sleep loss accumulates and can lead to shift work disorder or other chronic medical conditions. Hospitalists suffering from sleep deprivation also risk increased rates of medical errors. By realigning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 62 publications
1
14
1
Order By: Relevance
“…With our increasing knowledge of the impact of circadian disruptions and novel tools to study circadian phenotypes, such as the ones introduced in this study, effective interventions can be designed to minimize circadian disruption, stabilize circadian rhythmicity, and enhance well-being and performance [48,49]. Studies like this will provide athletes and coaches in the sports world with new insights that will allow them to improve performance, as well as also create awareness in the corporate world to adapt schedules to achieve maximum performance of the workforce and increase safety [50,51].…”
Section: Discussionmentioning
confidence: 97%
“…With our increasing knowledge of the impact of circadian disruptions and novel tools to study circadian phenotypes, such as the ones introduced in this study, effective interventions can be designed to minimize circadian disruption, stabilize circadian rhythmicity, and enhance well-being and performance [48,49]. Studies like this will provide athletes and coaches in the sports world with new insights that will allow them to improve performance, as well as also create awareness in the corporate world to adapt schedules to achieve maximum performance of the workforce and increase safety [50,51].…”
Section: Discussionmentioning
confidence: 97%
“…Some studies also recommend the use of caffeine, especially at the start of a night shift [ 62 , 77 ]. Beaumont and colleagues provided evidence for the positive effects of caffeine on vigilance (reported p < 0.01) and cognitive performance (reported p < 0.05) during a long wakefulness period [ 65 ].…”
Section: Reviewmentioning
confidence: 99%
“…Behavioral measures beyond improved sleep hygiene, such as exercise, can enhance sleep quality and combat insomnia and excessive sleepiness [ 53 ]. Most effective are the optimal timing of work breaks, social activities during breaks, and sensory stimulation, but those techniques still have to be evaluated within a shift work setting [ 62 ]. The post-intervention results of a study by Järnefeld and colleagues [ 71 ] showed significant improvements in self-reported (reported p = 0.002) and actigraphic (reported p < 0.05) sleep onset latency, self-reported sleep efficiency (reported p = 0.006), self-reported sleep quality (reported p < 0.001), and self-reported restedness (reported p < 0.05) through cognitive-behavioral strategies.…”
Section: Reviewmentioning
confidence: 99%
“…A misalignment between the circadian pacemaker and the sleep–wake cycle can result in a shift work disorder (Barger et al , ; Wright, Bogan, & Wyatt, ). Hospitalists can help to limit fatigue and improve performance and safety through circadian adaptation (Schaefer, Williams, & Zee, ). In other words, optimal timing of the nap that is taken after a night shift and the worker's bedtime that night not only prevents cumulative fatigue, but also could prevent disruption of the circadian rhythm and lower the risk of a shift work disorder.…”
Section: Discussionmentioning
confidence: 99%